2020
DOI: 10.1007/s10902-020-00267-z
|View full text |Cite
|
Sign up to set email alerts
|

Children’s and Adolescents’ Happiness Conceptualizations at School and their Link with Autonomy, Competence, and Relatedness

Abstract: Previous research on children's and adolescents' happiness either focused on their conceptualisations or the link between self-reported happiness with different outcomes.However, very few studies have connected both approaches to better understand children's and adolescents' happiness. To address this gap, we used a mixed-method approach, to investigate if the conceptualizations of happiness at school of 744 British children and adolescents could signal differences in autonomy, competence, and relatedness. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
2
0
1
Order By: Relevance
“…Eudaimonia was not significantly related to children's attainment, corroborating evidence that eudaimonia may be significantly associated with adolescents' but not children's attainment (Kryza-Lacombe et al, 2019;López-Pérez & Fernández-Castilla, 2018;López-Pérez & Zuffianò, 2021;Tobia et al, 2019). This is also consistent with research documenting a higher prevalence of hedonic motives among children compared to adolescents (Gentzler et al, 2021).…”
Section: Measures Matter When Examining Wellbeing and Attainmentsupporting
confidence: 81%
See 1 more Smart Citation
“…Eudaimonia was not significantly related to children's attainment, corroborating evidence that eudaimonia may be significantly associated with adolescents' but not children's attainment (Kryza-Lacombe et al, 2019;López-Pérez & Fernández-Castilla, 2018;López-Pérez & Zuffianò, 2021;Tobia et al, 2019). This is also consistent with research documenting a higher prevalence of hedonic motives among children compared to adolescents (Gentzler et al, 2021).…”
Section: Measures Matter When Examining Wellbeing and Attainmentsupporting
confidence: 81%
“…Examining age-related differences in wellbeing and attainment is therefore critical (Clarke, 2020). For example, one English study (López-Pérez & Zuffianò, 2021) found that ‘getting good grades’ was not significantly associated with children's life satisfaction at school but was associated with adolescents’. These developmental differences were also replicated in an earlier Spanish study (López-Pérez & Fernández-Castilla, 2018).…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…As long as a human subject believes that he/she is self-sufficient, they are bound for a solitary, isolated, and fundamentally unfulfilled lifeprovided that humans as personal beings are indeed essentially relational beings. (Lopez-Perez -Zuffiano, 2020) The acknowledgment of one's limitations is the first step to opening oneself up to the other in reciprocal acts of receiving and giving. Such is the common predicament of contingent beings in a contingent world.…”
Section: Examining the Role Of Transcendencementioning
confidence: 99%
“…Adolescent happiness is also associated with experiencing less violence or conflict, such as quarreling and bullying ( López-Pérez and Zuffianò, 2020 ). Uusitalo-Malmivaara and Lehto (2016) showed that bullying victims reported lower levels of well-being and happiness, with adolescents who experienced dual victimization (bullying and cyberbullying) reporting even more negative impact on their happiness and depression.…”
Section: Introductionmentioning
confidence: 99%